Metal plating and patination : cultural, technical, and historical developments - La Niece, Susan; Craddock, P. T. (Paul T.) (Butterworth-Heinemann, 1993)
Surface finishing is a major subject in the field of metals. The artistic and technical development of decorative or protective finishes has produced some distinctive classes of metalwork in different parts of the world. Metal Plating and Patination is the most important reference work to be published surveying the surface treatments used from the inception of metallurgy to the present day.